REINTEGRATION OF SCIENCE AND ISLAM IN ISLAMIC EDUCATION LEARNING IN URBAN MUSLIM COMMUNITIES - Usman Usman; Adamu Abubakar Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
Science and Islam were originally one in the realm of the unity of existence (al-wahidat al-wujud) Allah SWT. Still, when humans accepted them, they became multi-fragmented because of the capacity of each human mind. Islamic education, which originates from the Qur'an and Hadiths contributes to integrating Science and Islam. For this reason, this article aimed to explore the implementation of the reintegration of Science and Islam in postgraduate Islamic education learning at one of the Islamic tertiary institutions in Jambi province, Indonesia. This study used a qualitative approach to explore and understand the participants' experiences. The data were derived from the results of semi-structured interviews and free interviews, which explain and convey explicit or implied meanings or symbols from the collected data related to the steps for implementing three categories, namely the conception of knowledge, approaches to implementing the reintegration of Science and Islam in Islamic education learning, and materials used. The data were processed and analyzed using domain analysis to obtain an overview of the implementation of Science and Islamic reintegration in Islamic education. The study results explain that the strategic steps for implementing the reintegration of Science and Islam in Islamic education learning have three main aspects: The conception of science in the reintegration of Science and Islam in learning must be carried out to have one perception and one vision. That is, all knowledge comes from one source, namely Allah SWT. An approach to faith is based on a solid monotheism by combining and explaining signs found in nature (Kauniyah verses) with signs learned in the Qur'an and Hadith (Kauliyah verses). The Material comes from Science and Islam, the Qur'an, and Hadiths. Science as a social science is developed and linked to Islamic Science, the Qur'an, and Hadiths which form the basis of its development.